THU0564 Efficiency and safety evaluation of biosimilar infliximab for treatment of paediatric non-infectious uveitis in single centre. (12th June 2018) - Sozeri, B.; Kardes, E.; Bolac, L.G.; Sezgin Akçay, B.I.
Abstract : Background: Biosimilar infliximab (Remsima) has been introduced in our country, together with other European countries in 2014. Information regarding the use in child age group is limited but it is reported that its therapeutic efficiency and safety is similar to the reference molecule regarding the paediatric Chron disease Objectives: In this study, our aim was to reporte the efficiency and safety of BI used for children with non-infectious uveitis Methods: In this study, there were 13 subjects (9 boys, and 4 girls) diagnosed with non-infectious uveitis. BI (Remsima9 treatment had been given in 5 mg/kg in 0., 2., 4 th week and then every 8th week. Ophthalmic assessment of disease activity and ocular complications were measured throughout the trial with the use of slit-lamp biomicroscopy for uveitis activity, according to the SUN criteria. The Drug exposure has been evaluated by calculated of patient year (HY), adverse event (AE) was assessed using the CTCAE criteria. The median values due to the small number of patients are considered Results: The patients who were include the study, 5 had diagnosed extended oligo JIA, 2 with enthesitis-related arthritis (ERA), 2 with persistent oligo JIA, 2 with pars planitis and one of them Behcet's disease. At the time of evaluation, the median age was 10 years, 3–13 age at diagnosis of their disease 8 years, 1–13 respectively. The median age of uveitis diagnosis was 8 years. The median disease duration before BI was 10 months. All of the patients had methotrexate therapy with BI and BI before. Only one patient used a different biological agent prior to BI, and revealed they were determined that considered unresponsive. Other patients (n=12) had biosimilar infliximab as first biologic drug due to the activation of disease after using the drug methotrexate. After therapy of BI, in all of the patients, joint and eye symptoms were improvement. The systemic steroid therapy was cut down in the first month in all patients, 2 of them continue prophylactic topical steroids. The median duration of BI therapy was 10 months. There was one case of anaphylaxis in all the patients, whereas five of them frequent upper respiratory tract infection have been observed as side effect Conclusions: In this preliminary report, This biosimilar infliximab treatment appears to be safe and effective in paediatric age group on the paediatric patients with non-infectious uveitis. These results must be supported by multicenter studies and registries. Disclosure of Interest: None declared